PENGARUH KOMPETENSI DAN INDEPENDENSI TERHADAP KUALITAS AUDIT DENGAN ETIKA AUDITOR SEBAGAI VARIABEL PEMODERASI PADA BAWASDA PEMERINTAH DAERAH DI EX-KARESIDENAN SURAKARTA PROVINSI JAWA TENGAH - Monot Wicaksono (Jurnal Akuntansi dan Pajak, 2015)
The purpose of this research to know: 1) the effect on audit quality Bawasdacompetence, 2) the effect of competence on audit quality are moderated Bawasdaauditor ethics, 3) the effect of independence on audit quality Bawasda and 4) the effectof independence on audit quality are moderated Bawasda ethics auditors.The population in the study of all members Bawasda as internal audit thatconsists of 84 auditors in 7 (seven) districts in the territory of the Ex-Resident ofSurakarta, Central Java Province, the Municipality of Surakarta, Karanganyar district,Sragen, Wonogiri, Boyolali, Sukoharjo and Klaten, each numbered 12. Quota samplingrandom sampling of 70 respondents. To test the hypothesis used Regression Analysiswas with moderation.Results showed: 1) competence has a positive and significant impact on auditquality Bawasda, 2) moderate the influence of auditors' ethical competence of positiveand significant impact on audit quality Bawasda, 3) independence has a positive andsignificant impact on audit quality Bawasda 4) moderate the ethics of auditors influencethe independence of positive and significant impact on audit quality Bawasda as InternalAuditor at the Local Government Ex-Surakarta, Central Java Province.Keywords : Competence, Independence, Audit Quality, Ethics Auditor, Internal Auditor, Bawasda.